Implementing the Interaction Matric Method for Impact Assessment in Linear Infrastructure Project Planning: A Case Study of Route FT59 Jalan Tapah in Cameron Highlands, Malaysia (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Inadequate road design and construction without impact assessment has a negative influence on human well-being, as well as natural and non-living resources. It may have a number of detrimental effects on social and economic concerns. Social Impact Assessments (SIAs) are used to analyze, anticipate, and evaluate the social, economic, and environmental impacts on the impacted community. As a result, the purpose of this case study is to gather information on how impact assessment is considered in linear infrastructure construction by collecting census data for the route FT-59 Jalan Tapah, Cameron Highlands, Malaysia. All data was analyzed and presented using the Analytic Hierarchy Process (AHP) approach and Microsoft Excel utilizing a weighted combination of alternatives and criteria for ranking analysis. Results indicate the positive and negative impact of infrastructure development from local viewpoints in terms of social, economic, and environmental aspects at the pre-construction, construction, and operating phases. Furthermore, the results demonstrate the mitigation strategy for infrastructure facility construction. This results implies that organizations' main SIA practitioners should refer to this recommendation measure in order to enhance the outcome of SIA.